Sistem Pendukung Keputusan Pemilihan Admin Terbaik Menggunakan Metode Simple Additive Weighting Di Kantor CV Sragen - Pribadi Abthal; Muhammad Hasbi; Kumaratih Sandradewi (STMIK Sinar Nusantara, 2022)
This company always works hard to be at the forefront with modern service standards supported by professional Human Resources. Human Resource Management greatly affects employee dedication and performance. In this regard, the Company has not been able to optimize, especially in determining the best administrator (Admin). This is due to the absence of media that can process the best admin's judgment in the office. For this reason, it is necessary to apply the best admin support system using the Simple Additive Weighting (SAW) method. The definition of the Simple Additive Weighting (SAW) method is often also known as the weighted addition method. The basic concept of SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The purpose of this research is to find out the best admin every month, seen from the accuracy of work attendance, cooperation, discipline, and order. After the data was collected, HRDs can immediately use the calculation application using SAW method to determine the best admin. The test results obtained data that the best admin in CV office is A1 which has a value of 0.94.